Prenatal exposure to a low dose of BPS causes sex-dependent alterations to vascular endothelial function in adult offspring - Connors, Liam T.; Zhu, Hai-Lei; Gill, Manvir; Walsh, Emma; Singh, Radha D.; Easson, Sarah; Ahmed, Sofia B.; Habibi, Hamid R.; Cole, William C.; Thompson, Jennifer A. (Frontiers in Toxicology, 2022)
Background: Bisphenol S (BPS) is among the most commonly used substitute for Bisphenol A (BPA), an endocrine disrupting chemical used as a plasticizer in the manufacture of polycarbonate plastics and epoxy resins. Bisphenols interfere with estrogen receptor (ER) signaling, which modulates vascular function through stimulation of nitric oxide (NO) production via endothelial nitric oxide synthase (eNOS). BPS can cross into the placenta and accumulates in the fetal compartment to a greater extent than BPA, potentially interfering with key developmental events. Little is known regarding the developmental impact of exposure to BPA substitutes, particularly with respect to the vasculature. Objective: To determine if prenatal BPS exposure influences vascular health in adulthood. Methods: At the time of mating, female C57BL/6 dams were administered BPS (250 nM) or vehicle control in the drinking water, and exposure continued during lactation. At 12-weeks of age, mesenteric arteries were excised from male and female offspring and assessed for responses to an endothelium-dependent (acetylcholine, ACh) and endothelium-independent (sodium nitroprusside, SNP) vasodilator. Endothelium-dependent dilation was measured in the presence or absence of L-NAME, an eNOS inhibitor. To further explore the role of NO and ER signaling, wire myography was used to assess ACh responses in aortic rings after acute exposure to BPS in the presence or absence of L-NAME or an ER antagonist. Results: Increased ACh dilation and increased sensitivity to Phe were observed in microvessels from BPS-exposed females, while no changes were observed in male offspring. Differences in ACh-induced dilation between control or BPS-exposed females were eliminated with L-NAME. Increased dilatory responses to ACh after acute BPS exposure were observed in aortic rings from female mice only, and differences were eliminated with inhibition of eNOS or inhibition of ER. Conclusions: Prenatal BPS exposure leads to persistent changes in endothelium-dependent vascular function in a sex-specific manner that appears to be modulated by interaction of BPS with ER signaling.